CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Breaking the “Wall”: Mechanistic insights into low-intensity ultrasound (LIU)-induced recovery of calcified CANDAN granular sludge - Shenbin Cao; Yucheng Tao; Meng Zhang; Mingsheng Jia; Xiaoyan Fan; Rui Du; Yongzhen Peng (Water Research, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Species-specific modeling of tree diameter at breast height using tree height and relative density with implications for remote sensing-based forest inventory - Soheil Soheili Esfahani; Fan-Rui Meng; Christopher YS Wong (Forest Ecology and Management, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Integrated GNSS positioning and attitude determination with unscented Kalman filter - Xiangdong An; Xiaolin Meng; Yilin Xie; Fan Zhang; Liangliang Hu; Rui Shang (GPS Solutions, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

The occurrence and enrichment mechanism of indium in sphalerite from the Dachang Sn polymetallic ore field, South China: Part II. The Gaofeng deposit - Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Shi-Ni Fan; De-Feng Shi (Journal of Asian Earth Sciences, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Extraction of phenolic acids and tetramethylpyrazine in Shanxi aged vinegar base on vortex-assisted liquid-liquid microextraction-hydrophobic deep eutectic solvent: COSMO-RS calculations and ANN-GA optimization - Baoqing Bai; Siyuan Meng; Yanli Guo; Ziqing Zhang; Rui Chen; Tao Bo; Jinhua Zhang; Sanhong Fan; Yukun Yang (Food Chemistry, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Fe2O3@ZrO2 catalyst derived from MOF-on-MOF for direct CO2 hydrogenation to light olefins - Fan Xu; Xin Meng; Rui Zhao; Daoming Jin; Wenhua Dai; Dandan Yang; Zhong Xin (Chemical Engineering Journal, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

Assessing watershed-scale impacts of best management practices and elevated atmospheric carbon dioxide concentrations on water yield - Xiaoyu Kang; Junyu Qi; Charles P.-A. Bourque; Sheng Li; Chuan Jin; Fan-Rui Meng (Science of The Total Environment, 2024)

Titanium carbide-based nanocomposite: A promising reinforcing material for enzymatic CO2 conversion - Menglei Mao; Ruqing Chong; Feixue Sun; Rui Gao; Zihui Meng; Xinlong Fan; Wenfang Liu (Journal of Cleaner Production, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Impacts of re-vegetation on soil water dynamics in a semiarid region of Northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li (Science of The Total Environment, 2024)

Epsilon-poly-l-lysine alleviates brown blotch disease of postharvest Agaricus bisporus mushrooms by directly inhibiting Pseudomonas tolaasii and inducing mushroom disease resistance - Rui Song; Xiuhong Wang; Lu Jiao; Hanyue Jiang; Shuai Yuan; Lei Zhang; Zixuan Shi; Zhenchuan Fan; Demei Meng (Pesticide Biochemistry and Physiology, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Regulation of oxygen vacancy concentration over ZnCr oxide in bifunctional catalyst for the direct conversion of syngas to light olefins - Daoming Jin; Zhong Xin; Xin Meng; Wenhua Dai; Bowen Xu; Rui Zhao; Fan Xu; Dandan Yang (Chemical Engineering Journal, 2024)

Microalgae biofilm photobioreactor and its combined process for long-term stable treatment of high-saline wastewater achieved high pollutant removal efficiency - Gaozhong Fan; Jie Huang; Xin Jiang; Weile Meng; Rui Yang; Jinsong Guo; Fang Fang; Jixiang Yang (Journal of Environmental Chemical Engineering, 2023)

Highly dispersed Fe/EG catalysts assisted by ammonium citrate and their application in CO2 hydrogenation to olefins - Rui Zhao; Xin Meng; Wenhua Dai; Daoming Jin; Bowen Xu; Fan Xu; Dandan Yang; Zhong Xin (Fuel, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Yield responses of four common potato cultivars to an industry standard and alternative rotation in Atlantic Canada - Mohammad Amir Azimi; Yefang Jiang; Fan-Rui Meng; Kang Liang (American Journal of Potato Research, 2022)
This study was conducted to evaluate yield responses of four potato ( Solanum tuberosum L.) cultivars (‘Russet Burbank’, ‘Shepody’, ‘Gold Rush’, and ‘Russet Prospect’) and soil N dynamic changes to two 3-year rotations in Prince Edward Island, Canada. The two rotations were the local industry standard potato–barley ( Hordeum vulgare L. )–red clover ( Trifolium pratense L.) rotation (PBC) and an alternative potato–soybean ( Glycine max L.)–barley rotation (PSB). All potato cultivars received 170 kg N ha − 1 input at planting without irrigation. Soil mineral N content before potato planting was significantly higher under the PBC rotation. However, the PBC rotation produced significantly lower yields, suggesting the possibility of excessive N supply from the plowed-down red clover. While cultivar and the interaction between cultivar and rotation did not show a significant difference in yield, yields of all cultivars were positively affected by the PSB rotation. The Gold Rush cultivar was affected the most (36%), followed by Russet Burbank (17%) and Prospect (14%) cultivars, with Shepody being the least affected (3%) by the alternative PSB rotation. Russet Burbank was the highest yielding cultivar under both rotations. With the three russet cultivars combined as a single russet cultivar, the PSB rotation significantly increased tuber yields, while the Shepody cultivar did not significantly benefit from the PSB rotation, suggesting that the russet cultivars responded more sensitively to the alternative rotation. Results demonstrate that adequately accounting for N supply from a preceding green manure crop is required for sustainable potato production in this humid temperate region.

A novel amorphous solid dispersion based on drug–polymer complexation - Fan Meng; Rui Ferreira; Yongchao Su; Feng Zhang (Drug Delivery and Translational Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Aerobic degradation of 4-fluoroaniline and 2,4-difluoroaniline: performance and microbial community in response to the inocula - Zhi-Qing Zhao; Xiao-Meng Wei; Xiao-Li Shen; Ghulam Abbas; Rui Fan; Yi Jin (Biodegradation, 2021)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Reductions in water, soil and nutrient losses and pesticide pollution in agroforestry practices: a review of evidence and processes - Xiai Zhu; Wenjie Liu; Jin Chen; L. Adrian Bruijnzeel; Zhun Mao; Xiaodong Yang; Rémi Cardinael; Fan-Rui Meng; Roy C. Sidle; Steffen Seitz; Vimala D. Nair; Kazuki Nanko; et al. (Plant and Soil, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Genome editing in potato plants by agrobacterium-mediated transient expression of transcription activator-like effector nucleases - Jin Ma; Heng Xiang; Danielle J. Donnelly; Fan-Rui Meng; Huimin Xu; Dion Durnford; Xiu-Qing Li (Plant Biotechnology Reports, 2017)

SWAT Setup with Long-Term Detailed Landuse and Management Records and Modification for a Micro-Watershed Influenced by Freeze-Thaw Cycles - Junyu Qi; Sheng Li; Qi Yang; Zisheng Xing; Fan-Rui Meng (Water Resources Management, 2017)

Assessing an Enhanced Version of SWAT on Water Quantity and Quality Simulation in Regions with Seasonal Snow Cover - Junyu Qi; Sheng Li; Qiang Li; Zisheng Xing; Charles P.-A. Bourque; Fan-Rui Meng (Water Resources Management, 2016)

Projecting In-stream Dissolved Organic Carbon and Total Mercury Concentrations in Small Watersheds Following Forest Growth and Clearcutting - Chengfu Zhang; Rob C. Jamieson; Fan-Rui Meng; Robert Gordon; Charles P.-A. Bourque (Water, Air, & Soil Pollution, 2016)

Prioritizing Genes Related to Nicotine Addiction Via a Multi-source-Based Approach - Xinhua Liu; Meng Liu; Xia Li; Lihua Zhang; Rui Fan; Ju Wang (Molecular Neurobiology, 2015)

Estimation of potential impacts of climate change on growth and yield of temperate tree species - M. Irfan Ashraf; Charles P.-A. Bourque; David A. MacLean; Thom Erdle; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2015)

How do soil and water conservation practices influence climate change impacts on potato production? Evidence from eastern Canada - Thomas O. Ochuodho; Edward Olale; Van A. Lantz; Jerome Damboise; Jean-Louis Daigle; Fan-Rui Meng; Sheng Li; T. Lien Chow (Regional Environmental Change, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

A stand dynamic model for red pine plantations with different initial densities - Shusheng Li; Qingyu Hao; Edwin Swift; Charles P.-A. Bourque; Fan-Rui Meng (New Forests, 2011)

Impacts of Accuracy and Resolution of Conventional and LiDAR Based DEMs on Parameters Used in Hydrologic Modeling - Zhengyong Zhao; Glenn Benoy; Thien Lien Chow; Herb W. Rees; Jean-Louis Daigle; Fan-Rui Meng (Water Resources Management, 2010)

Assessing impact of projected future climate on tree species growth and yield: development of an evaluation strategy - Shaun Dombroskie; Monica McKendy; Courtney Ruelland; William Richards; Charles P.-A. Bourque; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2010)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Spatial extent of winter thaw events in eastern North America: historical weather records in relation to yellow birch decline - Charles P.‐A. Bourque; Roger M. Cox; Darren J. Allen; Paul A. Arp; Fan‐Rui Meng (Global Change Biology, 2005)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Combining carbon sequestration objectives with timber management planning - Fan-Rui Meng; Charles P.-A. Bourque; Steven P. Oldford; D. Edwin Swift; Helen C. Smith (Mitigation and Adaptation Strategies for Global Change, 2003)

Evaluating Critical Soil Acidification Loads and Exceedances for a Deciduous Forest at the Turkey Lakes Watershed - Mohammed Moayeri; Fan-Rui Meng; Paul A. Arp; Neil W. Foster (Ecosystems, 2001)

A New Height Growth Model for Dominant and Codominant Trees - Fan-Rui Meng; Chao Ho Meng; Shouzheng Tang; Paul A. Arp (Forest Science, 1997)
A model was developed to predict height growth for dominant and codominant trees, using asymptotic tree height, and tree height at the age of maximum height growth as principal characteristics to express the influence of site on tree height. The proposed model has many desirable attributes: it (1) produces polymorphic site-index curves, (2) contains an inflection point, (3) asymptotically approaches maximum tree height as age increases, (4) is mathematically defined at the point of origin, and (5) has a theoretical base (pipe model theory) for height growth. Model performance was evaluated with stem analysis data taken from naturally regenerated forest stands of mature to overmature balsam fir (Abies balsamea [L.] Mill.) and black spruce (Picea mariana Mill.) growing in two separate regions within New Brunswick, Canada. The model was also evaluated by analyzing its ability to reproduce existing site index curves for red pine (Pinus resinosa Ait.). The results indicate that the proposed model performs slightly better than an existing 5-parameter model based on the Richards' growth function. For. Sci. 43(3):348-354.